2016
DOI: 10.1111/ffe.12559
|View full text |Cite
|
Sign up to set email alerts
|

Local strain accumulation in fatigue crack propagation process of Ti‐6Al‐4V alloy

Abstract: Fatigue crack growth behaviours of the titanium alloy Ti‐6Al‐4V, with two different microstructures, at different maximum stresses were identified by digital image correlation technique. Full‐field strains were monitored around fatigue cracks after consecutive cycles in fatigue crack growth experiments. Results indicated that the Ti‐6Al‐4V alloy with a bi‐modal microstructure had a better fatigue resistance than that with a primary‐α microstructure. Typical behaviours of small cracks and the evolution of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…No facet feature is observed in the initiation region, displaying the typical failure type of “surface‐without‐facets.” 33 Meanwhile, radial stripes emanate around the microdefect. The generated stripes can be attributed to the laceration and are indicative of crack deflection through the propagation process 34 . Distribution and direction of the stripes are clearly presented in the stream‐type chart, as displayed in Figure 5C, which is generated from image binarization data of dash line area in Figure 5B.…”
Section: Fatigue Crack Initiation and Fracturementioning
confidence: 98%
See 1 more Smart Citation
“…No facet feature is observed in the initiation region, displaying the typical failure type of “surface‐without‐facets.” 33 Meanwhile, radial stripes emanate around the microdefect. The generated stripes can be attributed to the laceration and are indicative of crack deflection through the propagation process 34 . Distribution and direction of the stripes are clearly presented in the stream‐type chart, as displayed in Figure 5C, which is generated from image binarization data of dash line area in Figure 5B.…”
Section: Fatigue Crack Initiation and Fracturementioning
confidence: 98%
“…The generated stripes can be attributed to the laceration and are indicative of crack deflection through the propagation process. 34 Distribution and direction of the stripes are clearly presented in the stream-type chart, as displayed in Figure 5C, which is generated from image binarization data of dash line area in Figure 5B.…”
Section: Fractographic Analysismentioning
confidence: 99%
“…[31][32][33] When it comes to large-scale yielding, it is beyond the capacity of LEFM. Several studies [33][34][35] have demonstrated that the size of plastic zone is comparable with crack length in the initial stage of crack propagation. In the very beginning, the initial crack propagation is a large-scale yielding problem.…”
Section: Replacement Of δKmentioning
confidence: 99%